Percutaneous pharmacomechanical thrombectomy for acute iliofemoral deep vein thrombosis: A suitability study. (May 2015) - Nghiem, AZ; Rudarakanchana, N; Moore, HM; Davies, AH
Objectives: Percutaneous pharmacomechanical thrombectomy is an emerging therapy for acute deep vein thrombosis and may reduce long-term incidence of post-thrombotic syndrome. This study investigates the proportion of patients presenting with lower limb deep vein thrombosis who are potentially suitable for percutaneous pharmacomechanical thrombectomy. Methods: A retrospective review of all duplex ultrasound scans for lower limb deep vein thrombosis over two-year period at a regional vascular unit was conducted. All acute occlusive iliofemoral deep vein thrombosis were screened for percutaneous pharmacomechanical thrombectomy suitability according to predefined criteria. Results: There were 2513 duplex ultrasound scans for suspected lower limb deep vein thrombosis in the two-year period. There were 120 cases of acute occlusive iliofemoral deep vein thrombosis. After application of inclusion and exclusion criteria 48 out of 120 (40%) patients were identified as potential candidates for percutaneous pharmacomechanical thrombectomy. Conclusions: This indicates that a large randomised trial of percutaneous pharmacomechanical thrombectomy is feasible given expected recruitment rates in a multicentre study.